2015
DOI: 10.7150/jca.11371
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Analysis of Nine Chordoma Specimens by Targeted Next-Generation Cancer Panel Sequencing

Abstract: Background: Chordoma is a rare primary malignant bone tumour. Treatment options are mainly restricted to surgical excision, since chordomas are largely resistant to conventional ionising radiation and chemotherapy. Thus, there is a strong need to gain more thorough insights into the molecular biology and genetics of chordoma to allow for the development of new therapeutic options. We performed an ultra-deep sequencing analysis to find novel mutations in cancer associated genes in chordomas to date unseen with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Also, the four Chor-IN-1 tumor-specific variants were not present in the other chordoma cell lines. Therefore, we were unable to identify somatic mutations distinctive of chordoma, in line with what has already been published in literature 19 , 20 .…”
Section: Resultssupporting
confidence: 55%
“…Also, the four Chor-IN-1 tumor-specific variants were not present in the other chordoma cell lines. Therefore, we were unable to identify somatic mutations distinctive of chordoma, in line with what has already been published in literature 19 , 20 .…”
Section: Resultssupporting
confidence: 55%
“…Our work demonstrates that integrated and comprehensive DNA and RNA profiling is practical on archival chordoma samples and that such an approach aids in the identification of potential candidate therapeutic targets. Previous genetic studies of chordoma have reported somatic abnormalities in genes such as CDKN2A , PTEN , PIK3CA , and TP53 (Hallor et al 2008; Choy et al 2014; Fischer et al 2015; Wang et al 2016). Similar to previous studies, we did not observe highly recurrent somatic alterations; however, we identified alterations in genes that have been previously associated with chordoma, including PBRM1 (Wang et al 2016) and IGF1R (Sommer et al 2010; Scheipl et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses have led to the identification of pathological changes in chordomas. Such changes include transcriptomic changes (Bell et al 2016), as well as point mutations and copy-number losses in genes such as ALK , CDKN2A , NRAS , PTEN , NBPF1 , SETD2 , and SMARCB1 (Hallor et al 2008; Le et al 2011; Choy et al 2014; Fischer et al 2015; Wang et al 2016; Sa et al 2017; Cote et al 2018), whose loss characterizes poorly differentiated chordomas (Mobley et al 2010). Of note, loss of INI1/SMARCB1 may also represent a discrete entity with a more aggressive phenotype more similar to rhabdoid tumors (Hasselblatt et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous mutation screening studies in chordoma have been more limited in genomic scope. Choy et al studied 45 chordoma samples for 865 “hotspot” mutations in 111 oncogenes using the mass spectrum Sequenom iPLEX genotyping platform (Choy et al, ) and Fischer et al screened for mutations in 48 cancer genes on 9 chordoma samples using an amplicon‐based targeted next‐generation sequencing platform (Fischer et al, ). A few mutations were reported, however, the alteration frequency in their study set was extremely low, typically presenting in <2 samples in each study cohort.…”
Section: Discussionmentioning
confidence: 99%